Ethical dilemmas on social media: Swedish secondary teachers' boundary management on Facebook. Issue 2 (15th March 2018) - Thunman, Elin; Persson, Marcus
Abstract: With the aim of contributing to the research about the educational use of social media, the paper explores teachers' experiences of ethical dilemmas on Facebook. The paper draws upon focus group interviews with Swedish secondary teachers. Two main categories of ethical dilemmas, related to the border between private and professional, are detected. The dilemmas concern (1) teachers' moral responsibility for pupils' actions and (2) how teachers appear on social media. Different boundary work practices created and used by teachers are identified. The main conclusion is that, by having contact with pupils in a virtual social arena originally intended for private use, teachers' use of social media brings to fore and intensifies deep-rooted ethical questions about what the teacher role is and should be. Teachers' participation on social media such as Facebook compels them to reflect upon and position their preferred teacher role in these new social arenas.